One more new species of silverfish of the genus Ctenolepisma (Zygentoma: Lepismatidae) from India - Jana, Debanjan; Hazra, Ashis Kumar; Molero-Baltanás, Rafael; Mazumdar, Abhijit; Mandal, Guru Pada (Zootaxa, 2026)
A new species of the genus Ctenolepisma Escherich, 1905 is described from Maharashtra and Telangana, South India: Ctenolepisma (Ctenolepisma) tredecimum sp. nov. This species is compared with related previously described species belonging to the subgenus Ctenolepisma s. str. A key to the Indian species of the genus is provided.